The impact of knowledge management practice on the hospital performance in Abu Dhabi - Main Naser Alolayyan; Abdallah Hassan Alalawin; Mohammad S. Alyahya; Ahmad Qamar (Cogent Business & Management, 2020)
This study proposes a conceptual model that simultaneously involves five factors of Knowledge Management (KM) and six factors of Hospital Performance (HP), in their respective constructs. The significance of this model is that it has logically linked the constructs of both KM and HP. Exploratory factor analysis, reliability analysis procedure, and construct validity procedures have been used to verify and validate the underlying dimensions of KM and HP. The relationship has been analyzed through Structural Equation Modeling approaches, in the last stage of the data analysis, the results found that only three variables of KM construct have a significant directional impact on the only three variables of HP construct effects. Further, the in-depth data analysis has revealed that the three variables of KM construct have a statistically significant influence on the three variables of HP construct. The statistically rigorous and strong results obtained in this study suggest that this conceptual model can be used as a management tool to assess performance. The significant impact of KM on HP has been argued to be positive. The value of the paper is that it clarifies the influence of KM on HP in Abu-Dhabi hospitals which can be used to improve hospital performance and efficiency.
Keywords: 650; Knowledge Management (KM); hospital; performance; Abu-Dhabi; structure equation modeling